OVERVIEW OF INDONESIAN LAW AND INTERNATIONAL LAW ON TERRORISM AS AN EXTRAORDINARY CRIME - Nur Rohim Yunus; Siti Romlah; Siti Nurhalimah; Latipah Nasution (JHR (Jurnal Hukum Replik), 2022)
In terms of unusual crimes, terrorism is one of the most heinous acts. One only needs to look at the crimes that have been committed across national borders to recognize how devastating they can be for the victims and their families. The research method employed in this study is a combination of the Statute Approach and the Literature Approach. Since there are a variety of criminal activities that have been branded as terrorist crimes yet their perpetrators' goals and backgrounds differ, there is no agreed-upon definition of terrorism, according to a study. As an example of a crime that has been condemned as an act of international terrorism at the national level, the WTO event of September 11, 2001, and the Bali Bombing incident of 2002 come to mind. Therefore, it is imperative that all parties, including legal professionals, agree on the limitations of terrorism, as well as work together to prevent this unique crime from occurring.Keywords: Terrorism; National Law; International law; Extraordinary Crime